2017
DOI: 10.1071/mf16015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ramp slope and surface type on the climbing success of shortfin eel (Anguilla australis) elvers

Abstract: Instream structures such as dams, weirs and culverts reduce diadromous fish (e.g. freshwater eels) biodiversity and abundance by restricting upstream migrations. Fish passes are used to facilitate fish passage around instream structures, but limited information is available about design aspects that influence the ability of fish to negotiate the structures. We used experimental ramps to evaluate the effects of surface type and slope on the climbing success of shortfin eel (Anguilla australis) elvers (total len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
2
23
1
Order By: Relevance
“…Despite the results presented here, indicating a low efficiency of eel ramps in facilitating upstream migration, the literature contains several reports of efficient implementations (Briand et al, ; Knights & White, ; Legault, ; Solomon & Beach, ). Studies also show that manipulating certain design features can have fundamental impacts on the success of eel ramps (Anwar, ; Drouineau et al, ; Jellyman et al, ; Kerr et al, ; Piper et al, ; Watz, Nilsson, Degerman, Tamario, & Calles, ). This knowledge needs to be transformed, however, into conservation action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the results presented here, indicating a low efficiency of eel ramps in facilitating upstream migration, the literature contains several reports of efficient implementations (Briand et al, ; Knights & White, ; Legault, ; Solomon & Beach, ). Studies also show that manipulating certain design features can have fundamental impacts on the success of eel ramps (Anwar, ; Drouineau et al, ; Jellyman et al, ; Kerr et al, ; Piper et al, ; Watz, Nilsson, Degerman, Tamario, & Calles, ). This knowledge needs to be transformed, however, into conservation action.…”
Section: Discussionmentioning
confidence: 99%
“…Birnie-Gauvin et al, 2018). Experimental studies on the passage of juvenile eels show that small modifications in ramp design or properties, such as hydraulics, type of attraction flow, substrate type, slope, and placement can create dramatic changes in passage efficiency (Drouineau et al, 2015;Jellyman, Bauld, & Crow, 2017;Piper, Wright, & Kemp, 2012), and omitting evaluations will contribute to the continued operation of measures with suboptimal FPS efficiency (Birnie-Gauvin et al, 2018).…”
Section: Figurementioning
confidence: 99%
“…Upstream passage solutions for juvenile eels instead take advantage of the eels’ rheotactic and thigmotactic climbing behaviour (Jellyman, ; Geffroy & Bardonnet, ) and generally consist of an inclined ramp lined with a wetted climbing substratum (Solomon & Beach, ) with an attraction flow at the entrance of the ramp (Piper, Wright & Kemp, ). The features of the ramps, such as climbing substratum and slope, are critical, as the efficiency in aiding the ascent of juvenile eels (both in terms of passage success rate and climbing velocity) may directly affect the performance of the passage solution (Jellyman et al ., ; Anwar, ). Evaluations of single substrata have shown that, for example studded plastic tiles and bristle passes improve passage success at Crump weirs (Kerr et al ., ; Vowles et al ., , ), but few studies have directly compared the performance of different climbing substrata (Jellyman et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The features of the ramps, such as climbing substratum and slope, are critical, as the efficiency in aiding the ascent of juvenile eels (both in terms of passage success rate and climbing velocity) may directly affect the performance of the passage solution (Jellyman et al ., ; Anwar, ). Evaluations of single substrata have shown that, for example studded plastic tiles and bristle passes improve passage success at Crump weirs (Kerr et al ., ; Vowles et al ., , ), but few studies have directly compared the performance of different climbing substrata (Jellyman et al ., ). A recent study by Tamario et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation